Species-specific double-strand break repair and genome evolution in plants - Kirik, Angela (Oxford University Press, 2000)
Even closely related eukaryotic species may differ drastically in genome size. While insertion of retroelements represents a major source of genome enlargement, the mechanism mediating species- specific deletions is fairly obscure. We analyzed the formation of deletions during double-strand break (DSB) repair in Arabidopsis thaliana and tobacco, two dicotyledonous plant species differing >20-fold in genome size. DSBs were induced by the rare cutting restriction endonuclease I-SceI and deletions were identified by loss of function of a negative selectable marker gene containing an I-SceI site. Whereas the partial use of micro-homologies in junction formation was similar in both species, in tobacco 40% of the deletions were accompanied by insertions. No insertions could be detected in Arabidopsis, where larger deletions were more frequent, indicating a putative inverse correlation between genome size and the average length of deletions. Such a correlation has been postulated before by a theoretical study on the evolution of related insect genomes and our study now identifies a possible molecular cause for the phenomenon, indicating that species-specific differences in DSB repair might indeed influence genome evolution.